2014
DOI: 10.2903/j.efsa.2014.3667
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of fumonisin esterase (FUMzyme®) as a technological feed additive for pigs

Abstract: FUMzyme® is an enzyme‐based feed additive intended to degrade fumonisin mycotoxins found as contaminants in feeds for growing pigs. It is produced from a genetically modified strain of Komagataella pastoris. The viable production strain and its recombinant genes are not present in the final product. Piglets showed no adverse effect when given feed containing 15‐times the maximum recommended dose. Consequently the FEEDAP Panel concludes that the additive is safe for pigs when used within the dose range proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The safety and efficacy of this additive for use in pigs and poultry feed were evaluated by the FEEDAP Panel in 2018 (EFSA FEEDAP Panel, 2018a). The safety and efficacy of the same enzyme produced by Komagataella pastoris DSM 26643 were the subject of other two opinions of the FEEDAP Panel (EFSA FEEDAP Panel, 2014, 2016.…”
Section: Additional Informationmentioning
confidence: 99%
“…The safety and efficacy of this additive for use in pigs and poultry feed were evaluated by the FEEDAP Panel in 2018 (EFSA FEEDAP Panel, 2018a). The safety and efficacy of the same enzyme produced by Komagataella pastoris DSM 26643 were the subject of other two opinions of the FEEDAP Panel (EFSA FEEDAP Panel, 2014, 2016.…”
Section: Additional Informationmentioning
confidence: 99%
“…The product under assessment is an enzyme-based additive intended to degrade fumonisin mycotoxins found as contaminants of feed. The safety and efficacy of the enzyme expressed in a different host from that used in the present application were the subjects of two previous opinions: the first, published in 2014, considered its use in feeds for pigs (EFSA FEEDAP Panel, 2014) and the second in 2016 its use in feed for all avian species (EFSA FEEDAP Panel, 2016). This additive is currently authorised for use in pigs 3 and avian species (1m03).…”
Section: Additional Informationmentioning
confidence: 96%
“…A number on in vitro studies made with FB1 considered in the previous opinions of the FEEDAP Panel showed that the action of fumonisin esterase resulted in partial or complete de-esterification, releasing tricarballylic acid and the fully or partially de-esterified aminopentol backbone (EFSA FEEDAP Panel, 2014, 2016. Although FB1 and FB2 are the most prevalent fumonisins, a total of eight are recognised differing only by the number and position of hydroxyl groups on the aminopentol backbone.…”
Section: Enzyme Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…The safety and efficacy of the additive when used in feed to pigs was the subject of an opinion published in 2014 (EFSA FEEDAP Panel, 2014). The safety and efficacy of the additive when used in feed to pigs was the subject of an opinion published in 2014 (EFSA FEEDAP Panel, 2014).…”
Section: Additional Informationmentioning
confidence: 99%